Improved water resource management using an acoustic pulsed Doppler sensor in a shallow open channel - Cook, Mike, author; Huhta, Craig, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
Over the years, acoustic Doppler profilers (ADP) have become a standard for flow measurement in large open channels. In most cases, pulsed Doppler systems measure the water-velocity profile either from the side of the channel or from a bottom-mounted system. Having a velocity profile is critical in providing accurate flow measurements and provides important information about the structure of the velocities in the flow. These systems are often optimized for different sizes of open channels by using different acoustic frequencies, acoustic beam configurations as well as other factors, however, ADPs have been traditionally too expensive for flow monitoring in small channels. Traditional alternatives to ADP for measurements in small channels have used water level as a surrogate or continuous wave acoustic instruments. These two technologies, although inexpensive, do present problems to end users in the form of accuracy, which can be a major problem when making decisions or billing based on the collected data. Building on the success of ADPs in open channels and considering the increasing demand to quantify flows in very small channels due to the increasing scarcity of water, SonTek developed a shallow water flow meter - the SonTek IQ - for open channels ranging from 0.08 m to 5 meters in depth. The new flow meter uses multiple beams to measure water velocity and applies a vertical beam and pressure sensor to measure water level - these two types of data are used to calculate flow. In addition to the new design, the IQ provides improved performance for theoretical flow calculations, which are important in smaller channels, such as ditches and turnouts where an index calibration may not be practical when considering cost. This paper describes the sensor configuration, preliminary specifications and theoretical flow models used to calculate open channel discharge. Preliminary testing in flow laboratories demonstrated good agreement when compared to independent measurements.
Irrigated agriculture responds to water use challenges
Acoustic pulsed Doppler sensor
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.